Antardvandva: in Urvashi Khandakavya - Pokhrel, Thakur Prasad (Adhyayan Journal, 2023)
This article examines the development of conflict in the characters of Siddhicharan Shrestha’s Urvashi Khandakavya. Urvashi was captivated by Arjun’s brilliance and courage after he reached Indralok, who was in exile, and she was attracted by his arrival. She intends to accomplish her mission by entering Arjuna’s bedroom in a state of desire. Khandakavya is based on the context of Arjuna, who is on the verge of attaining the goals of truth, justice, and victory by mastering his senses. Due to Arjuna and Urvashi’s divergent aspirations, conflict has developed in the Khandakavya. Based on subheadings, this article analyzes the topic introduction, conflict theory, historical context of conflict, categories of conflict, conflict in Urvashi Khandakavya, positive-positive conflict, negative-negative conflict, positive-negative conflict, etc. What kinds of problems do the poem’s protagonists face? The conclusion has been reached that there is a contradiction between poetry and the academic problem-solving endeavor.